Hepatic Arterial Infusion Chemotherapy of Oxaliplatin, Fluorouracil, and Leucovorin With or Without Sorafenib as Initial Treatment for Advanced Hepatocellular Carcinoma - Liang, Run-Bin; Zhao, Yang; He, Min-Ke; Wen, Dong-Sheng; Bu, Xiao-Yun; Huang, Ye-Xing; Lai, Zhi-Cheng; Xu, Yu-Jie; Kan, Anna; Wei, Wei; Zhang, Yao-Jun; Chen, Min-Shan; et al. (Frontiers in Oncology, 2021)
Purpose: Our previous study showed that hepatic arterial infusion chemotherapy (HAIC) using oxaliplatin, fluorouracil, and leucovorin (FOLFOX) plus sorafenib provided a significant survival benefit over sorafenib for advanced hepatocellular carcinoma. However, it is unclear whether the survival benefit should be attributed to the synergism between HAIC and sorafenib or just HAIC alone. We aim to compare HAIC using FOLFOX plus sorafenib with HAIC alone in patients with advanced hepatocellular carcinoma. Materials and Methods: This was a retrospective study including 225 eligible patients treated with HAIC using FOLFOX (HAIC alone group, n=126, oxaliplatin 85 mg/m², leucovorin 400 mg/m², fluorouracil bolus 400 mg/m² and 2400 mg/m² for 46 hours, every 3 weeks) alone or HAIC plus sorafenib (soraHAIC group, n=99, sorafenib 400 mg twice daily). Survival curves were calculated by the Kaplan-Meier method, and propensity-score matching was used to reduce bias. Results: The soraHAIC group showed a longer overall survival (12.9 [95% CI, 10.4-15.4] vs. 10.5 [95% CI, 9.5-11.5] months, HR 0.71 [95% CI, 0.53-0.96]; P=0.025), a better progression free survival (7.0 [95% CI, 5.3-8.8] vs. 5.3 [95% CI, 3.5-7.1] months, HR 0.76 [95% CI, 0.58-0.99]; P=0.046), and a higher disease control rate (RECIST 1.1: 74.8% vs. 61.1%, P=0.030) than the HAIC alone group. In multivariate analysis, soraHAIC was an independent favor factor for survival. In terms of the grade 3/4 adverse event, hand–foot skin reaction was more frequent in the soraHAIC group than the HAIC alone group. In the propensity-score matched cohorts (93 pairs), the overall survival, the progression free survival and disease control rates in the soraHAIC group were also better than those in the HAIC group (P<0.05). Conclusion: HAIC plus sorafenib may improve overall survival and progression free survival compared with HAIC alone as initial treatment for advanced hepatocellular carcinoma.